The Impact of Endoscopic Linear Stapling Device Stability in Thoracic Surgery: A Delphi Panel Approach - Daniel Miller; Diego Gonzalez Rivas; Kellie L. Meyer; Ryan S. Clark; Tadasu Kohno (Journal of Health Economics and Outcomes Research)
**Objectives:** To develop consensus statements outlining the impact of endoscopic linear stapling device stability on potential complications of thoracic surgery and the stress/concern of thoracic surgeons.